Cleaning Officers’ Behavior in Waste Management According to The Standards of Accreditation in X Jember Hospital - Carri Noer Fida Yanik; Dwi Wahyuni; Dewi Rokhmah (Health Notions, 2019)
Waste management is very important especially in hospitals. Hospital waste management must be done properly and correctly so that it can be prevented from diseases caused by waste that will be felt by all residents of the hospital. The purpose of this study was to analyze factors related to the behavior of cleaning officers in waste management in X Jember Hospital. The research design used was cross sectional. The results showed that age, education, years of service, knowledge and supervision were related to the behavior of cleaning officers in waste management with p value of